Successful Indonesian startups’ product blogs: A digital genre analysis and its pedagogical implications - Nugrahaningtyas Fatma Anyassari; Novitasari; Tri Astuti Handayani; Cita Nuary Ishak; Nafisya Alfiani Aisyah (UNIB Press, 2023)
Blogs can be deemed as an alternative digital media which have been strategically employed for business communication. One of the realizations is product blogs. As startups, which are identically linked to digital media, have been skyrocketing in number, product blogs play an integral role to accommodate their business communication. In writing an article for the product blogs, startups often open an internship vacancy for, among others, polytechnic students majoring English for business communication. However, generic structure of a product blog article is quite different from academic essays. There is a need to equip the students with adequate product blog article writing skills before they embark on internship. This study aims at empirically delving into generic structure of successful Indonesian startups’ product blogs. To achieve the aim, this research employed corpus-based research methodology. There were 33.430 tokens of product blogs from two unicorn startups. The framework for analysis was adapted from Askehave and Nielsen (2005). The findings show that there were three moves in the corpus, namely contextualizing product, detailing product, and soliciting response. Each move consisted of steps which were categorized into reading mode and navigating mode. The findings lead to pedagogical implications—inculcating the moves to polytechnic students majoring English for business communication—as an attempt to link and match between vocational pedagogy and industry requirements.